PERFORMANCE OF INVESTMENT MANAGEMENT: A STUDY ON SOCIAL ISLAMI BANK LIMITED (SIBL) - Tasnim, Sanzida; Islam, Ariful (International Journal of Islamic Banking and Finance Research, 2021)
This study attempts to understand the level of efficiency of investment management of social Islami bank limited (SIBL). In this regards, different aspects (i.e., amount, ratio, profit and growth) of deposit, investment, investment modes and procedures are scrutinized thoroughly. To conduct the study, secondary data sources have been primarily used. Some information was also collected from officials over the phone. The study was based on five consecutive years i.e., 2015 to 2019.The major findings are that the ratio of investment deposit also remains as high as 90%. The bank invests more in Murabaha, Bai-Muazzal, HPSM and Quard. The ratio of classified investment to total investment increased 8.20% till 2017 and decrease to 6.63% up to 2019 whereas the ratio of unclassified investment decrease to 89.09% till 2017 and increase to 91.71% up to 2019. There has an increase of sub-standard and doubtful investments till 2017 and a decrease up to 2019. But in case of bad or loss investment, an upward trend has been observed till 2018 and had a negligible decrease in 2019. The last part of the analysis shows that the overall profit growth of investment fluctuated over years but remains positive i.e., 11.39%. In conclusion, the bank is moderately efficient in investment management. JEL Classification Codes: G11, G24, O16.